Opportunity costs of forest set-asides in Poland : a case study of Sulechow Forest District - Lysiak, Piotr (SLU/Southern Swedish Forest Research Centre, 2009)
Due to the world’s increasing scarcity of different dimensions of biodiversity there is a constant need for finding the right balance between economical concerns and nature conservation in forestry. The management of natural resources requires a good assessment of the productive stand value as well as costs of forgone opportunity. Such costs appear when setting the areas aside for nature conservation purposes. In this thesis calculations of opportunity costs of set-asides were based on differences in the holding value among three management scenarios with increasing level of restrictions: